Authors at the boundary: Interaction of local and general scientific literature - Baskici, Cigdem; Atan, Suat; Ercil, Yavuz (Malaysian Journal of Library and Information Science, 2018)
How a scientific literature is shaped both at the local and general level is an important question to answer. One practical way of achieving this task is to identify the roles played by authors (academicians) as actors creating and disseminating knowledge in the relevant literature. To this end, this study examines roles undertaken by authors in the field of learning organizations. Identifying role typologies first requires revealing the author citation network in the field. Citation network is a matrix that summarizes citations and citation numbers between authors. To construct this matrix, articles in the local and general literature in the field of learning organizations, published and indexed between January 01, 2015 and February 20, 2017, were collected from Google Scholar by using the Java-based Selenium Library. An author citation network with 19,525 actors was created from this list. A social network analysis was conducted to identify author roles, followed by a discussion of what these roles mean for the local literature. Despite defining four typologies, observing only one type of role typology indicates that the local literature is not well integrated with the general literature. This study recommends strategic assessments for increasing the contribution ability of local literature to general one. Using this approach, it would be possible to find answers to the questions of which roles to develop via which authors and relationships, and how to remove the obstacles to development of local literature.